KOLABORASI SISWA DALAM PEMBELAJARAN MATEMATIKA DENGAN PENDEKATAN REALISTIC MATHEMATICS EDUCATION (RME) : MEMBANGUN PEMAHAMAN KONSEP MELALUI KONTEKS NYATA - Hasanah, Uswatun; Erna Yayuk (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
Technological developments are a challenge for the world of education, because changes in information are increasingly rapid. So students' competency needs are also increasingly complex. 21st Century Learning Design (21st Century Learning Design) is a learning model framework developed to improve 21st century skills. This goal has an important role in ensuring that the education provided not only prioritizes academic achievement, but also creates space for the development of 21st century skills. , one of which is collaboration. This research uses descriptive qualitative methods. The subjects of this research were 5th grade students at SD Muhammadiyah 29 Surabaya. The aim of this research is to describe student collaboration in learning mathematics using the Realistic Mathematics Education (RME) approach. Data collection for this research used interviews, questionnaires and observations. The results of this research show that students work together very well, have good joint responsibility, are able to make substantive decisions in determining the volume formulas for cubes and blocks and have sufficient ability to depend on each other. So the level of collaboration of grade 5 students at SD Muhammadiyah 29 Surabaya shows collaboration at level 4 of the 21st Century Learning Design Rubric.